2019
DOI: 10.1039/c9sc01078e
|View full text |Cite
|
Sign up to set email alerts
|

Optimal coordination-site exposure engineering in porous platinum for outstanding oxygen reduction performance

Abstract: Optimal coordination-site exposure engineering in porous platinum brings ultrahigh activity and durability for the fuel cell oxygen reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 38 publications
1
32
1
Order By: Relevance
“…Some important progress in recent years has been made in the development of porous Pt‐based ORR electrocatalysts, in which the intrinsic activity of the catalytic sites is optimized by tuning the local coordination environment around the Pt atoms. [ 70 ] For example, Cheng et al reported the synthesis of grain boundary‐rich, porous Pt electrocatalyst consisting of 3 nm nanocrystals by a confined space pyrolysis strategy ( Figure a). [ 70a ] Their DFT calculation demonstrated that the Pt sites at the grain boundaries had a higher coordination number than those on isolated Pt grains (Figure 9b), and this was supported by X‐ray absorption fine structure (XAFS) analysis.…”
Section: Porous Orr Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some important progress in recent years has been made in the development of porous Pt‐based ORR electrocatalysts, in which the intrinsic activity of the catalytic sites is optimized by tuning the local coordination environment around the Pt atoms. [ 70 ] For example, Cheng et al reported the synthesis of grain boundary‐rich, porous Pt electrocatalyst consisting of 3 nm nanocrystals by a confined space pyrolysis strategy ( Figure a). [ 70a ] Their DFT calculation demonstrated that the Pt sites at the grain boundaries had a higher coordination number than those on isolated Pt grains (Figure 9b), and this was supported by X‐ray absorption fine structure (XAFS) analysis.…”
Section: Porous Orr Electrocatalystsmentioning
confidence: 99%
“…[ 70 ] For example, Cheng et al reported the synthesis of grain boundary‐rich, porous Pt electrocatalyst consisting of 3 nm nanocrystals by a confined space pyrolysis strategy ( Figure a). [ 70a ] Their DFT calculation demonstrated that the Pt sites at the grain boundaries had a higher coordination number than those on isolated Pt grains (Figure 9b), and this was supported by X‐ray absorption fine structure (XAFS) analysis. This allowed the former to exhibit more optimal adsorption energies toward oxygenated species during ORR.…”
Section: Porous Orr Electrocatalystsmentioning
confidence: 99%
“…It has been demonstrated that the performance of catalysts strongly depends on the surface structures [15][16][17][18][19][20]. In particular, previous studies demonstrated that the catalytic structures rich in grain boundaries usually exhibit high catalytic activities, such as ORR, CO2 reduction reaction (CO2RR), and methanol oxidation reaction (MOR) [13,[21][22][23][24]. The grain boundaries can be developed inside polycrystalline crystals, but the density is usually scarce because of the consequent lattice distortion induced instability [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…At present, Pt is still the efficient ORR and HER catalysts because of its high electrocatalytic performance. But the amounts of Pt need to reach 20 wt.% and even 20-40 wt.% for using as HER and ORR catalysts, respectively, which limits the practical application due to its limited reserve and high price [6,7]. Although Pt-free electrocatalysts, such as phosphides [8], chalcogenides [9], oxides [10,11], nitrides [12] and carbon based materials [13], have shown promising HER and/or ORR activities, it is rather difficult to completely replace Pt with these catalysts due to the significant gap in performance between the present state-of-the-art Pt-based catalysts and the Pt-free catalysts.…”
Section: Introductionmentioning
confidence: 99%